Four dangers in innovation policy studies – and how to avoid them. Issue 2 (17th February 2016) - Flanagan, Kieron; Uyarra, Elvira
Abstract: The field of innovation policy studies is at a crossroads. It has clearly been influential. However, might it be losing the critical insight necessary to remain so in future? We discuss four dangerous tendencies seen in many innovation policy studies: idealising policy rationales and policy-makers; treating policies as tools from a toolbox; putting too much faith in coordination and intelligent design of 'policy mixes'; and taking an atemporal approach to innovation policy. Based on these we identify some ways forward that, we argue, would deal better with the complex multi-actor dynamics, fundamental uncertainties and challenges to the implementation, coordination and evaluation of policies and which would make for more relevant and impactful innovation policy studies.